2016
DOI: 10.1152/jn.00366.2016
|View full text |Cite
|
Sign up to set email alerts
|

Masking reduces orientation selectivity in rat visual cortex

Abstract: In visual masking the perception of a target stimulus is impaired by a preceding (forward) or succeeding (backward) mask stimulus. The illusion is of interest because it allows uncoupling of the physical stimulus, its neuronal representation, and its perception. To understand the neuronal correlates of masking, we examined how masks affected the neuronal responses to oriented target stimuli in the primary visual cortex (V1) of anesthetized rats (n = 37). Target stimuli were circular gratings with 12 orientatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 57 publications
2
18
2
Order By: Relevance
“…The lack of effect of ISI on lapse rate also argues against a cognitive mechanism for the effects of ISI on behavior. Finally, the disproportional increase in threshold (and decrease in FA rates) with suppression of V1 is consistent with effects of ISI on behavior acting through effects on sensory coding, and not through more cognitive mechanisms like forward masking and attentional blink (Raymond et al, 1992;Macknik and Livingstone, 1998;Alwis et al, 2016). Notably, these phenomena also tend to act on much shorter time-scales (tens of milliseconds) than intervals used in this study, making them unlikely candidates to explain the effects of ISI on behavior.…”
Section: °4supporting
confidence: 80%
“…The lack of effect of ISI on lapse rate also argues against a cognitive mechanism for the effects of ISI on behavior. Finally, the disproportional increase in threshold (and decrease in FA rates) with suppression of V1 is consistent with effects of ISI on behavior acting through effects on sensory coding, and not through more cognitive mechanisms like forward masking and attentional blink (Raymond et al, 1992;Macknik and Livingstone, 1998;Alwis et al, 2016). Notably, these phenomena also tend to act on much shorter time-scales (tens of milliseconds) than intervals used in this study, making them unlikely candidates to explain the effects of ISI on behavior.…”
Section: °4supporting
confidence: 80%
“…In an electrophysiological investigation of visual masking in anaesthetized Long Evans rats, we showed that in primary visual cortex, neuronal responses to oriented circular gratings were altered by the presentation of a mask with analogous trends to those observed in other mammalian species (Alwis et al, ; Bridgeman, , ; Kovács et al, ; Rolls et al, ). Population decoding of these data allowed us to reliably predict orientation in a coarse discrimination task (e.g., horizontal vs. vertical), and decoding performance decreased when a mask was presented (Dell, Arabzadeh, & Price, ).…”
Section: Introductionsupporting
confidence: 62%
“…Visual masking therefore offers a powerful tool to investigate the neuronal correlates of perception. The neuronal mechanisms responsible for visual masking are unclear, but likely involve a complex interaction of mechanisms occurring throughout the retina, thalamus and cortex (Alwis, Richards, & Price, 2016;Fehmi, Adkins, & Lindsley, 1969;Levick & Zacks, 1970;Rolls, Tovee, & Panzeri, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the disproportional decrease in FA rates (and increase in threshold) with suppression 433 of V1 is consistent with effects of ISI on behavior acting through effects on sensory coding, and 434 not through more cognitive mechanisms like forward masking and attentional blink (Raymond et 435 al., 1992;Macknik and Livingstone, 1998;Alwis et al, 2016). Notably, these phenomena also 436 tend to act on much shorter time-scales (tens of milliseconds) than intervals used in this study, 437 making them unlikely candidates to explain the effects of ISI on behavior.…”
mentioning
confidence: 86%